AN ANALSYSIS OF THE STUDENTS’ PERCEPTION ON GOOGLE CLASSROOM FOR LEARNING ENGLISH - Surmiyati; Asma Ul Husna Hamid; Rahayu Apriliaswati (UIBU, 2022)
This study investigated the students' perception on using Google Classroom (GC) for learning English at SMAN 2 Sungai Raya. This research was a descriptive study with a quantitative approach; survey method involving 146 eleventh grade students at SMAN 2 Sungai Raya. The data were analyzed using descriptive statistics for the close-ended questions. The findings were presented the total mean score of five indicators of close-ended questions and distribution frequency table based on the theme of open-ended questions. The result presented that the total mean score of each indicators showed positive responses. Those were the usefulness of GC features (M=3.72), the ease of use of the features to motivate the students (M=3.71), Students’ participation (M=3.66), and students’ satisfaction (M=3.54). These can be approved by the students’ statements that learning English using GC was fun and improved their English reading and writing skills. The result showed that students had positive perceptions towards the use of GC.